2000
DOI: 10.1162/089976600300015510
|View full text |Cite
|
Sign up to set email alerts
|

A Phase Model of Temperature-Dependent Mammalian Cold Receptors

Abstract: We present a tractable stochastic phase model of the temperature sensitivity of a mammalian cold receptor. Using simple linear dependencies of the amplitude, frequency, and bias on temperature, the model reproduces the experimentally observed transitions between bursting, beating, and stochastically phase-locked firing patterns. We analyze the model in the deterministic limit and predict, using a Strutt map, the number of spikes per burst for a given temperature. The inclusion of noise produces a variable numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Spike bursts evoke higher levels of synaptic neurotransmitter compared to single spikes more sparsely distributed in time. Additionally, bursts might enable more precise information transfer compared to single spikes because spike burst patterns can drive higher neurons more efficiently (Roper et al, 2000;Krahe and Gabbiani, 2004). The central nervous system is able to discriminate between temporal spike train patterns, which have the same mean firing rate but correspond to different temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Spike bursts evoke higher levels of synaptic neurotransmitter compared to single spikes more sparsely distributed in time. Additionally, bursts might enable more precise information transfer compared to single spikes because spike burst patterns can drive higher neurons more efficiently (Roper et al, 2000;Krahe and Gabbiani, 2004). The central nervous system is able to discriminate between temporal spike train patterns, which have the same mean firing rate but correspond to different temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…This model has seen increasing interest in recent years among theoreticians, primarily because the QIF neuron has the same properties as any type I neuron whenever the ring rate is low (Ermentrout & Kopell, 1986;Ermentrout, 1996). Among other studies, Roper, Bressloff, and Longtin (2000) studied the critical slowing down and stochastic resonance/trapping effects that occur close to the saddle-node bifurcation. QIF neurons have also been used in network studies: Latham, Richmond, Nelson, and Nirenberg (2000) studied the equilibrium properties of the background state of large networks, and Mato (2001, 2003) studied the synchronization properties of networks of QIF neurons in the absence of noise.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from those conductance-based models, a fully ionic model has been proposed by Longtin and Hinzer [ 5 ], which discussed the stochastic action potential phase model specifically for a cat's lingual cold receptor. This model was further simplified by Roper et al [ 14 ], namely, by introducing a simplified phase differential equation. It was demonstrated that the corresponding model was able to approximate the Longtin-Hinzer model for temperature interval 17.8°C to 40°C.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the corresponding model was able to approximate the Longtin-Hinzer model for temperature interval 17.8°C to 40°C. Compared to the conductance-based model, Roper's model [ 14 ] offered a relatively simple mathematical description. However, we discovered that this model did not lead to a realistic description on phenomena that occurred in higher or lower temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation